Prince Hidayatullah-Based Learning Model for Student Character Development - Mansyur; Budimansyah, Dasim; Wahyu; Nurdin, Encep Syarief (LifeSciFi, 2025)
The issue of character development in higher education remains a crucial challenge in preparing students to become responsible and value-driven individuals. To address this, local historical figures can serve as exemplary models in the learning process, particularly in strengthening students’ moral and cultural foundations. This study aims to develop and examine the effectiveness of the Prince Hidayatullah Exemplary-Based Learning Model as an alternative approach to character education in universities. A qualitative approach with descriptive-qualitative methods was employed to explore the implementation and outcomes of the model. The findings reveal that the model effectively fosters key values, including responsibility, nationalism, integrity, and religiosity. The role of local historical figures proved to be a strong medium for emotional and cultural internalization of values, influencing students’ attitudes and behaviors. The study concludes that integrating exemplary figures into value-based curricula is highly relevant to the current educational context. Moreover, it emphasizes the importance of reflective learning as a strategy for character formation. This model not only aligns with the Merdeka Belajar policy but also offers a contextually grounded framework for strengthening character in higher education.